Role of Anonychium africanum (Plantae, Fabaceae) in Metal Oxido-Inflammatory Response: Protection Evidence in Gonad of Male Albino Rat - Harrison A. Ozoani; Orish Ebere Orisakwe; Costantino Parisi; Loredana Assisi; Anthonet N. Ezejiofor; Kenneth O. Okolo; Chinna N. Orish; Rubina Vangone; Emidio M. Sivieri; Giulia Guerriero (MDPI AG, 2024)
Male fertility is strongly affected by the overexpression of free radicals induced by heavy metals. The aim of this study was to evaluate the potential antioxidant, anti-inflammatory, and gonado-protective effects of natural compounds. Biochemical and morphological assays were performed on male albino rats divided into five groups: a control group (water only), a group orally exposed to a metal mixture of Pb-Cd-Hg-As alone and three groups co-administered the metal mixture and an aqueous extract of the Nigerian medicinal plant, Anonychium africanum (Prosopis africana, PA), at three different concentrations (500, 1000, and 1500 mg/kg) for 60 days. The metal mixture induced a significant rise in testicular weight, metal bioaccumulation, oxidative stress, and pro-inflammatory and apoptotic markers, while the semen analysis indicated a lower viability and a decrease in normal sperm count, and plasma reproductive hormones showed a significant variation. Parallel phytochemical investigations showed that PA has bioactive compounds like phlobatannins, flavonoids, polyphenols, tannins, saponins, steroids, and alkaloids, which are protective against oxidative injury in neural tissues. Indeed, the presence of PA co-administered with the metal mixture mitigated the toxic metals' impact, which was determined by observing the oxido-inflammatory response via nuclear factor erythroid 2-related factor 2, thus boosting male reproductive health.